Numerical technique based on transfer matrix method for prediction of muffler performance / Mohd A'zmi Yunus - Yunus, Mohd A'zmi (2008)
Mufflers are commonly used for automobile exhaust systems to attenuate the noise levels produced by automobile engine to atmosphere. Since a muffler plays an important part in attenuating the noise level in an automobile exhaust system, reliable, superior and affordable procedures and methods are applied for the analysis of a muffler is the main focus of this study. This study presents an alternative method to analyse the noise performance of a muffler with different configurations and parameters. The prediction of the Transmission Loss (TL) of muffler is the item of interest in the analysis of the noise performance. Computing source code is developed based Transfer Matrix Method (TMM).The formulation was derived from plane wave and acoustic theory, which utilised for accurate prediction of the Transmission Loss (TL) of the muffler. The efficiency and accuracy of the Transfer Matrix Method was illustrated by comparing the numerical results of Transmission Loss (TL) with the results obtained from establish papers and journal. The numerical results showed very good agreement with the results presented in the previous published journals.